The Effect of Healthy Lifestyle and Role Stress On Auditor Performance With Emotional Quotient As the Moderating Variable - M. Rifkhi Fauzan; Sitti Fatimah Kamaruddin (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2022)
This study aims to examine the effect of healthy lifestyle and role stress on auditor performance with emotional quotient as moderating variable. Respondents in this study is auditors who work for Inspectorate of South Sulawesi Province, Indonesia. The total population consisted of 60 auditors and the technique of determining the sample was cencus method, which is the entire population were used as a research samples. In this study the method used was explanatory research. Data collection used a questionnaire instrument. Data were analyzed using Moderated Regression Analysis (MRA). The result show that healthy lifestyle positively and significantly affects auditor performance. Role stress are negatively and significantly affects auditor performance. Further analysis found that Emotional quotient mediates the relationship among healthy lifestyle and role stress on auditor performance.